THE COMPANY STRATEGY IN IMPROVING THE WORK ENVIRONMENT TO MAXIMISE EMPLOYEES SATISFACTION AND PERFORMANCE - Siti Mariam (Yayasan Education and Social Center, 2023)
This research aims to reveal the strategies used by companies to improve the work environment with the aim of maximizing employee satisfaction and performance. Employee satisfaction and performance are two key factors that have a significant impact on a company's success and sustainability. This research uses a qualitative approach with case studies of several companies that have succeeded in improving the work environment and achieving high levels of employee satisfaction and performance. The research method will involve in-depth interviews with senior managers and employees who have relevant experience in these companies. The results of this research conducted by several companies operating in the heavy equipment supply business in West Jakarta reveal various strategies that have been used by successful companies to create a work environment that supports employee productivity and happiness. These findings provide valuable insights for company management to increase the job satisfaction and performance of their employees through improving the work environment and better efforts to meet employee needs and expectations. The implications of this research can also be used as a guide for other companies in their efforts to maximize employee potential through better human resource management strategies